Imaging inflammatory plasma leakage in vivo - Kenne, Ellinor; Lindbom, Lennart (Thrombosis and Haemostasis, 2011)
Increased vascular permeability and consequent plasma leakage from postcapillary venules is a cardinal sign of inflammation. Although the movement of plasma constituents from the vasculature to the affected tissue aids in clearing the inflammatory stimulus, excessive plasma extravasation can lead to hospitalisation or death in cases such as influenza-induced pneumonia, burns or brain injury. The use of intravital imaging has significantly contributed to the understanding of the mechanisms controlling the vascular permeability alterations that occur during inflammation. Today, intravital imaging can be performed using optical and non-optical techniques. Optical techniques, which are generally used in experimental settings, include traditional intravital fluorescence microscopy and near-infrared fluorescence imaging. Magnetic resonance (MRI) and radioisotopic imaging are used mainly in the clinical setting, but are increasingly used in experimental work, and can detect plasma leakage without optics. Although these methods are all able to visualise inflammatory plasma leakage in vivo, the spatial and temporal resolution differs between the techniques. In addition, they vary with regards to invasiveness and availability. This overview discusses the use of imaging techniques in the visualisation of inflammatory plasma leakage.
Keywords: Inflammation; imaging; endothelial cells